Huellas del pasado en las culturas escolares - Rockwell, Elsie (Revista de Antropología Social, 2007)
Assuming an anthropological concept that underscores the historical dimension of culture, the article argues that school cultures can be understood in terms of the selective and progressive appropriation of diverse cultural resources. To sustain this position, it examines practices observed towards the end of the twentieth century in elementary schools of a Nahuatl region of Mexico. Analyses of interviews and classroom transcripts reveal the influence of educational precepts and reforms introduced during the whole century, including the effects of successive textbooks. Practices also reflect the incorporation of discursive and cultural resources from the region. The historicity of school practices would challenge the existence of a constant and uniform “culture of schooling” and rather advises undertaking careful comparative research.